The mitochondrial genomes of the caddisflies Sericostoma personatum and Thremma gallicum (Insecta: Trichoptera). (2nd September 2016) - Dietz, Lars; Brand, Philipp; Eschner, Lisa Marie; Leese, Florian
Abstract: The mitochondrial genomes of the caddisfly species Sericostoma personatum and Thremma gallicum were sequenced on a 454 FLX and Illumina MiSeq platform, respectively. Reads were assembled de novo and remaining gaps in the S. personatum mitogenome closed by Sanger sequencing. The lengths of the assembled mitogenomes were 15, 260 bp and 15, 343 bp for S. personatum and T. gallicum, respectively. Both mitogenomes contained all 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and the control region. The mitochondrial gene order of both caddisflies is identical with the typical insect gene order. These are the third and fourth published mitogenomes of the order Trichoptera of two formerly unexplored families and thus will be useful in future phylogenetic analysis.